A follow-up approach to manage tachyarrhythmia and bradyarrhythmia in Ebstein’s anomaly patient - Setyowati, Danti Utami; Ardian Rizal (Heart Science Journal, 2025)
Background: Ebstein’s Anomaly (EA) is a rare heart defect that can cause a number of problems, including arrhythmias. They exhibit a greater rate of recurrence compared to those with normal hearts. High-definition (HD) mapping and three-dimensional (3D) ablation are new techniques that may be suboptimal, attributed to anatomical characteristics. The management tactics employed may necessitate modification in accordance with personal traits. Case Report: A 37-year-old male presented with intermittent palpitations over years. The electrocardiogram (ECG) is changing overtime such as supraventricular tachycardia (SVT), ventricular tachycardia (VT) and atrial fibrillation (AF). Echocardiography shown typical features of EA. During ablation, multiple atrial tachycardias were induced. Throughout the observation period, the patient exhibited complications related to several arrhythmia recurrence. In the end he suffered from total atrioventricular block (TAVB), leading to the decision to undergo a permanent pacemaker procedure. We postulated that specific characteristics of the right atrioventricular groove structure observed in pathological samples of EA could explain less than ideal results in ablation procedures. Conclusion: Managing arrhythmia in EA could be challenging. A prominent ridge alongside the lower atrioventricular groove is a typical characteristic in EA, and is associated with the clinical background of accessory pathways (AP). Understanding this anatomical aspect is important for electrophysiologists who work with this group of patients, since their management approaches may need to be adjusted.